Desa Pekerja Bangunan: Pemberdayaan Masyarakat Menuju Desa Penghasil Pekerja Bangunan Profesional Dan Bersertifikat Dengan Pemasaran Jasa Online Di Kelurahan Gunungpati - Agustinus Sungsang Nana Patria; Dwi Sulistiyawati; Brian Dwi Riswanto; Tabita Vinesia Damai Yanti; Wafik Nur Maulina; Adibah Sulistiyoningsih; Fariha Fatmawati Rini Nur Aini; Noor Mohammad Hatta; Immanuel Elang Artha Putra; Aleda Elly; Kevin Dwi Andriansyah; Wisnu Rahmat Penjawi; Akhmad Amiq Sauqi Adhim (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The needs of construction workers play a very important role in society. However, based on the results of a survey of several construction workers from Gunungpati Village, problems were found such as never having received socialization and training, not having a craftsman skills certificate, lack of interest in learning and literacy among the residents, not really knowing the construction workers from Gunungpati Village and marketing of construction worker services is still conventional. To answer these problems, PPK Ormawa BEM Faculty of Engineering, University of 17 August 1945 Semarang implemented construction worker empowerment programs in the Gunungpati sub-district such as the "Construction Worker Socialization and Training" program, "Construction Worker Certification", construction of the "Construction Education House", "Gunungpati Building Cities” and “Marketing Online Construction Worker Services”. The results obtained from the implementation of the program were that 68 construction workers had received socialization and training, 10 construction workers had BNSP light steel applicator certificates, 28 construction workers had paint applicator certificates, a construction library was built, namely the Construction Education House, an increase in interest in learning from 33 % to 74%, increase in the level of recognition of construction workers from Gunungpati sub-district from 56% to 82%, marketing of online construction worker services using 3 social media, namely Instagram, Facebook and Whatsapp, and 10 construction workers have been ordered to construction companies. Apart from that, it produces a spirit of independence and awareness of the potential of society. Formation of construction workers' associations and collaboration between implementation teams, student organizations, universities, communities, sub-districts, departments, associations, construction companies and vendors.